Blocking of orexin receptors in the paraventricular nucleus of the thalamus has no effect on the expression of conditioned fear in rats - Dong, Xinwen; Li, Yonghui; Kirouac, Gilbert J. (Frontiers in Behavioral Neuroscience, 2015)
The paraventricular nucleus of the thalamus (PVT) projects to the central nucleus of the amygdala and recent experimental evidence indicates a role for the PVT in conditioned fear. Furthermore, the PVT contains a high density of orexin receptors and fibers and acute injections of orexin antagonist into the PVT produce anxiolytic effects. The present study was done to determine if administration of a dual orexin receptor antagonist (DORA) in the region of the PVT interfered with the expression of conditioned fear in rats exposed to cued and contextual conditioning paradigms. Infusion of 0.5 µl of the DORA N-biphenyl-2-yl-1-{[(1-methyl-1H-benzimidazol-2yl) sulfanyl] acetyl}-L-prolinamide at a concentration of 0.1, 1.0, and 10 nmol had no effect on the freezing produced by exposing rats to an auditory cue or the context associated with foot shock. In contrast, the 1.0 and 10 nmol doses were anxiolytic in the social interaction test. The results of the present study do not support a role for orexin receptors in the PVT in the expression of learned fear. The finding that the 1.0 and 10 nmol doses of DORA in the PVT region were anxiolytic in the social interaction test is consistent with other studies indicating a role for orexins in the PVT in anxiety-like behaviors.